Performance of selected natural dyes on Yucca-blended fabrics in forms of colorfastness to washing and light - Cabase, Athina Maricar M. (College of Home Economics, University of the Philippines Diliman, 2019)
The Philippine Textile and Research Institute (PTRI) is focusing its efforts to address issues regarding sustainable textiles through several research projects, one which dealt with Dracaena Spathiphyllum (Yucca), a source of natural fiber. PTRI also conducts studies to reviving natural dyeing in the country. This experimental study aimed to determine the performance of selected natural dyes when applied to Yucca blended fabric in terms of colorfastness to washing and light. Specifically, the study constructed plain woven fabrics in four fiber compositions, 100% cotton, 70% cotton/30% yucca, 100% polyester, and 70% polyester/30% yucca, dyed these fabrics using Annato, Buko and Talisay in two different concentrations (250% and 500%) and two soaking times (30 minutes and 60 minutes), and conducted home laundering and drying experiments to assess their colorfastness to washing and light. Fiber extraction, fabric construction, and the dyeing processes were done by PTRI. The laundering and drying were conducted by the researcher using home techniques. The washed and dried fabrics were then assessed by the PTRI testing laboratory in terms of color change after washing and after drying under the sun using the AATCC Gray Scale for Color Change. Results show that the 250% dye concentration displayed higher colorfastness to washing and light than the 500% dye concentration. Buko dye displayed the highest colorfastness to washing and light compared to Annato and Talisay. The 70% polyester/30% yucca blend fabric displayed the highest colorfastness to light compared to the other four fabrics. The researcher recommends to use other fiber compositions and different concentration of the same natural dyes to further investigate the most efficient combination of fiber blends and dyes with good colorfastness to washing and light.